2015
DOI: 10.1017/pasa.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

The γ-ray Pulsar J0633+0632 in X-rays

Abstract: We analysed Chandra observations of the bright Fermi pulsar J0633+0632 and found evidence of an absorption feature in its spectrum at 804 +42 −26 eV (the errors are at 90% confidence) with equivalent width of 63 +47 −36 eV. In addition, we analysed in detail the X-ray spectral continuum taking into account correlations between the interstellar absorption and the distance to the source. We confirm early findings that the spectrum contains non-thermal and thermal components. The latter is equally well described … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 54 publications
(90 reference statements)
5
21
0
Order By: Relevance
“…We analysed the XMM-Newton observations of the J0633 γray pulsar. We confirmed previous investigations (Ray et al 2011;Danilenko et al 2015) that the pulsar spectrum contains thermal and non-thermal components. The former can be equally well fitted by either the blackbody or magnetized neutron star atmosphere models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We analysed the XMM-Newton observations of the J0633 γray pulsar. We confirmed previous investigations (Ray et al 2011;Danilenko et al 2015) that the pulsar spectrum contains thermal and non-thermal components. The former can be equally well fitted by either the blackbody or magnetized neutron star atmosphere models.…”
Section: Discussionsupporting
confidence: 92%
“…For these two models, our results are generally consistent with the results of that work, while the parameter uncertainties obtained here are much smaller. To our surprise, we found no evidence of the absorption spectral feature at 0.8 keV in the XMM-Newton data, whose presence in the Chandra data was claimed by Danilenko et al (2015). This becomes clear from examination of the residuals of the spectral fit by a purely continuum spectral model presented in Fig.…”
Section: Spectra Of J0633 and Its Pwnmentioning
confidence: 52%
“…The general procedure is outlined e.g., in Section 2.1 of Danilenko et al (2015) and https://asd.gsfc.nasa.gov/ XSPECwiki/statistical_methods_in_XSPEC tended emission partially overlaps with one of MOS 1's damaged CCDs, and MOS2 has fewer net counts than the pn. Following the approach taken by, e.g., Younes et al (2016), we first extracted the background spectrum from the region shown by the dashed white circle in Figure 1.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Numbers 1 -41 enumerate the entries in Table 3 of Potekhin et al (2015). We have updated the data for object 4 according to Posselt et al (2013) and added objects 42 (XMMU J173203.3−344518, Klochkov et al 2015), 43 (CXOU J181852.0−150213, Klochkov et al 2016), and 44 (PSR J0633+0632, Danilenko et al 2015;Karpova et al 2017). The errorbars and arrows for magnetars are drawn in red color.…”
Section: Cooling Of Nonmagnetized Neutron Starsmentioning
confidence: 99%
“…For the thermal luminosity of the neutron star CXO J232327.9+584842 in the supernova remnant Cassiopeia A (object number 4, often dubbed Cas A NS) we have adopted improved observational data onL (Posselt et al 2013). We have supplemented this catalog with three neutron stars with recently measured thermal fluxes: two neutron stars with carbon envelopes (sources 42 and 43, Klochkov et al 2015Klochkov et al , 2016, and one pulsar (source 44, Danilenko et al 2015;Karpova et al 2017; in this case, we adopt the interpretation of the thermal spectrum with the model of a partially ionized magnetized hydrogen atmosphere nsmax, Ho et al 2008). Objects 25 through 41 (red symbols) are magnetars.…”
Section: Cooling Of Nonmagnetized Neutron Starsmentioning
confidence: 99%